Дослідження спектральних властивостей скломатриці оптичного кольорового скла для інтерференційного фільтру - Петров, Дмитро Вікторович; Брагіна, Людмила Лазарівна; Філоненко, Сергій Вікторович (НТУ "ХПІ", 2017)
Розглянуто сучасний стан виробництва безкольорових та кольорових оптичних стекол для оптико-електронних систем ОЕС. Показана актуальність створення вітчизняного інфракрасного скла для використання його як інтерференційного фільтру в ОЕС приладів оборонної галузі. Встановлено фактори, що відповідають за забезпечення повного поглинання у ультрафіолетовій та видимій частинах спектру та максимальне пропускання такого скла при довжині хвилі 1060 нм. Наведені результати досліджень зі створення скломатриць інфракрасних стекол з вказаними характеристиками, високою якістю виробів з них та з відпрацювання технологічних параметрів їх одержання.

The current state of colorless and colored optical glasses production for optoelectronic systems is considered. The actuality of creating domestic infrared glass for use as an interference filter in optoelectronic systems of defense detachments is shown. The aim of the work is to create a glass matrix of infrared optical glass with an intrinsic refractive index τ = 90% at a wavelength λ = 1060 ± 20 nm. In work the standard methods of spectral analysis, the determination of the number and size of bubbles and fibrils in glass are used. The experimental glass compositions were melted in an electric furnace with silicon carbide heaters. The factors responsible for providing full absorption in the UV and visible parts of the spectrum and maximum transmission at a wavelength of 1060 nm are established. The results of studies on the development of infrared glasses with these characteristics and high quality of the products from them are worked out. The possibility of creating a boron-containing and aluminium-containing technological and cost-effective glass matrix with a refractive index of τ = 91.5% and τ = 92.8%, respectively, at a wavelength λ = 1060 ± 20 nm is established. The technological parameters of their production have been worked out. All this is the basis for the development of domestic optical colored infrared glass of a new generation, which will act as an interference filter in optoelectronic systems.
Investigation of the glass matrix spectral properties of the optical color glass for interference filter
Keywords: оптичне скло; інфракрасне оптичне скло; спектральні характеристики; оптико-електронні системи; інфрачервоний спектр; коефіцієнт пропускання; infrared optical glass; spectral characteristics; optoelectronic devices